Mechanical properties of foldable thermoplastic composite connector - LIU Yuxi; CHEN Yu; LIU Shaozhu; JING Xianghai (Cailiao gongcheng)
An aramid fiber reinforced thermoplastic resin composite connector was developed for the connection of trenchless penetration repair lining pipe of ocean pipeline. The results of the hydrostatic burst test show that the failure mode under internal pressure is that the fiber of the pipe itself breaks and the connector remains intact. The tensile test results show that the tensile strength of the connector is higher than that of the lining pipe body， which meets the requirements of penetration construction. The internal pressure， tensile and folding models of the composite connector were established， and the ultimate strength， stress and strain distribution， and variation trend of the lining pipe and connector were predicted by finite element analysis. The finite element results show that the main bearing structure under internal pressure is the toroidal fiber， and the maximum strain occurs at the junction of the connector and the lining pipe body. The main load-bearing structure under tensile action is axial fiber， and the outer thermoplastic polyurethane edge has a large strain due to stress concentration， but it is still within the limit elastic strain range of the material. During the large deformation process of folding and unfolding， the maximum strain occurs in the folding stage， and the intermediate connector strain is close to the strain at lining pipe body. The intermediate connector of the pipe body developed in this study is convenient to manufacture， exhibits a high degree of compatibility with the lining pipe， and can be continuously coiled and folded， meeting the requirements of one-time long-distance repair of submarine pipelines.